In vitro cholinesterase enzymes inhibitory potential and in silico molecular docking studies of biogenic metal oxides nanoparticles. Issue 9 (2nd September 2018) - Khalil, Ali Talha; Ayaz, Muhammad; Ovais, Muhammad; Wadood, Abdul; Ali, Muhammad; Shinwari, Zabta Khan; Maaza, Malik
Abstract: The inhibition of Acetylcholinesterase (AChE) and Butyrylcholinesterase (BChE) enzymes represents a potential target in the treatment of Alzheimer disease. AChE and BChE inhibition was studied by biogenic metal oxide nanoparticles (ZnO, NiO, Fe2 O3, Co3 O4 and PbO) synthesized using aqueous extracts of Sageretia thea (Osbeck.). The results demonstrated that the highest inhibition was shown by PbO nanoparticles with the IC50 values of 101.9 µg/mL for AChE and 119.8 µg/mL for BChE. Furthermore, the results obtained from molecular docking studies analyzing the interaction of nanoparticles with enzymes, were in good agreement with the experimental data.